Uncharted digenean diversity in Lake Tanganyika: cryptogonimids (Digenea: Cryptogonimidae) infecting endemic lates perches (Actinopterygii: Latidae) - Kmentová, Nikol; Bray, Rodney A; Koblmüller, Stephan; Artois, Tom; De Keyzer, Els Lea R; Gelnar, Milan; Vanhove, Maarten P M; Georgieva, Simona (Parasites & vectors, 2020)
BACKGROUND: Lake Tanganyika is considered a biodiversity hotspot with exceptional species richness and level of endemism. Given the global importance of the lake in the field of evolutionary biology, the understudied status of its parasite fauna is surprising with a single digenean species reported to date. Although the most famous group within the lake's fish fauna are cichlids, the pelagic zone is occupied mainly by endemic species of clupeids (Actinopterygii: Clupeidae) and lates perches (Actinopterygii: Latidae, Lates Cuvier), which are an important commercial source for local fisheries. In this study, we focused on the lake's four lates perches and targeted their thus far unexplored endoparasitic digenean fauna. METHODS: A total of 85 lates perches from four localities in Lake Tanganyika were examined. Cryptogonimid digeneans were studied by means of morphological and molecular characterisation. Partial sequences of the nuclear 28S rRNA gene and the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene were sequenced for a representative subset of the specimens recovered. Phylogenetic analyses were conducted at the family level under Bayesian inference. RESULTS: Our integrative approach revealed the presence of six species within the family Cryptogonimidae Ward, 1917. Three out of the four species of Lates were found to be infected with at least one cryptogonimid species. Two out of the three reported genera are new to science. Low interspecific but high intraspecific phenotypic and genetic diversity was found among Neocladocystis spp. Phylogenetic inference based on partial 28S rDNA sequences revealed a sister group relationship for two of the newly erected genera and their close relatedness to the widely distributed genus Acanthostomum Looss, 1899. CONCLUSIONS: The present study provides the first comprehensive characterisation of the digenean diversity in a fish family from Lake Tanganyika which will serve as a baseline for future explorations of the lake's digenean fauna. Our study highlights the importance of employing an integrative approach for revealing the diversity in this unique host-parasite system.
Keywords: Biodiversity; mitochondriální DNA; DNA, Mitochondrial; druhová specificita; Species complex; Cichlids; Neocladocystis biliaris n. sp.; fylogeneze; Bayes Theorem; Lakes; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; biodiverzita; sekvenční analýza DNA; infekce červy třídy Trematoda; biologická evoluce; respirační komplex IV; sekvenční seřazení; Species Specificity; jezera; Tanganyikatrema n. g.; Electron Transport Complex IV; RNA ribozomální 28S; cichlidy; Animals; Tanzanie; Biological Evolution; zvířata; Trematoda; Tanzania; Grandifundilamena n. g.; Bayesova věta; Neocladocystis bemba n. sp.; Gills; Trematode Infections; DNA, Ribosomal; RNA, Ribosomal, 28S; žábry; Sequence Alignment